2003
DOI: 10.1111/j.1349-7006.2003.tb01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in colorectal cancer and in vitro chemosensitivity to 5‐fluorouracil: A study of 88 surgical specimens

Abstract: To predict the sensitivity of colorectal cancer to 5-fluorouracil (5-FU), we compared the gene expression of surgically obtained colorectal cancer specimens with chemosensitivity to 5-FU as detected by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H tetrazolium bromide (MTT) assay. Eighty-eight patients with advanced and/or metastatic colorectal cancer provided written informed consent and entered the trial from September 2000 to October 2001. Fresh surgical specimens were used for the MTT assay, and sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Enhanced activity of DPD is known to endow tumor cells with resistance to 5-FU in vitro and in clinical studies [22,23,24,25]. Using 88 surgical specimens, Yoshinare et al [22] demonstrated that high DPD mRNA expression is associated with low sensitivity to FU-based chemotherapy in metastatic colorectal cancer patients. Moreover, the activation and regulation of the DPD gene are also of great interest in predicting the efficacy of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced activity of DPD is known to endow tumor cells with resistance to 5-FU in vitro and in clinical studies [22,23,24,25]. Using 88 surgical specimens, Yoshinare et al [22] demonstrated that high DPD mRNA expression is associated with low sensitivity to FU-based chemotherapy in metastatic colorectal cancer patients. Moreover, the activation and regulation of the DPD gene are also of great interest in predicting the efficacy of 5-FU.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] Low levels of DPD mRNA expression has also been associated with a low sensitivity to 5-FU and has also been correlated with a low sensitivity to fluoropyrimidine-based chemotherapy in colorectal cancer patients. [36][37][38][39] TS as well as DPD is an enzyme that plays key roles in 5-FU resistance in carcinoma cells. High intratumoral TS mRNA levels are believed to confer 5-FU resistance due to resulting inefficient TS inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU is converted into its inactive metabolite fluoro-5,6-dihydrouracil (FUH 2 ) by dihydropyrimidine dehydrogenase (DPYD) (37). TS and DPYD gene expression and/or activity are major determinants of the efficacy of 5-FU (38,39).…”
mentioning
confidence: 99%